Implementation Of The Teaching At The Right Level (Tarl) Approach In Improving Students' Learning Interest In Pai Subjects: A Case Study At Sdn Cipeuyeum 04 Cianjur - Wati Irnawati; Danabillah Ilmiah (Pasundan Social Science Development, 2026)
This research is motivated by the phenomenon of low emotional involvement and interest of students in Islamic Religious Education (PAI) learning, especially in students who experience a lag in understanding the material compared to their peers. The purpose of this study is to describe in depth how the implementation of the Teaching at the Right Level (TaRL) approach is implemented and analyze the dynamics of changes in student learning interest after this approach is implemented. This research uses a qualitative method with a case study type at SDN Cipeuyeum 04 Cianjur. The research subjects were selected purposively, including PAI teachers and fifth grade students who have varying learning abilities. Data collection techniques were carried out through participant observation, in-depth interviews, and documentation, with data analysis using the Miles and Huberman interactive model. The results of the study show that: (1) The implementation of TaRL changes interaction patterns in the classroom to be more inclusive through ability-based grouping; (2) Students' learning interest grows due to a sense of psychological safety, where students no longer feel embarrassed or afraid of making mistakes; (3) Personalization of materials eliminates cognitive pressure, thereby changing passive students into participatory ones.